Physical oceanography of Seahorse profiler and CARIOCA buoy at station HL2 at the Scotain Shelf in 2007 and 2014 - Thomas, Helmuth; Greenan, Blair; Lemay, Jonathan (PANGAEA, 2018)
The understanding of the seasonal variability of carbon cycling on the Scotian Shelf in the NW Atlantic Ocean has improved in recent years; however, very little information is available regarding its short-term variability. In order to shed light on this aspect of carbon cycling on the Scotian Shelf we investigate the effects of Hurricane Arthur, which passed the region on 5 July 2014. The hurricane caused a substantial decline in the surface water partial pressure of CO2 (pCO2), even though the Scotian Shelf possesses CO2-rich deep waters. High-temporal-resolution data of moored autonomous instruments demonstrate that there is a distinct layer of relatively cold water with low dissolved inorganic carbon (DIC) slightly above the thermocline, presumably due to a sustained population of phytoplankton. Strong storm-related wind mixing caused this cold intermediate layer with high phytoplankton biomass to be entrained into the surface mixed layer. At the surface, phytoplankton begin to grow more rapidly due to increased light. The combination of growth and the mixing of low DIC water led to a short-term reduction in the partial pressure of CO2 until wind speeds relaxed and allowed for the restratification of the upper water column. These hurricane-related processes caused a (net) CO2 uptake by the Scotian Shelf region that is comparable to the spring bloom, thus exerting a major impact on the annual CO2 flux budget.